School leaders' engagement with the concept of evidence-based practice as a management tool for school improvement. (July 2016) - Sheard, Mary K.; Sharples, Jonathan
Strategies that encourage direct linkage and exchange between researchers and practitioners are more likely to support changes in educational practice informed by research evidence. Nevertheless, significant challenges remain in linking effectiveness education research to real-world practice: addressing the knowing–doing gap. The paper describes and evaluates an enquiry with a small network of three primary schools to demonstrate a 'proof-of-concept' for evidence-informed practice. The enquiry evaluated the effectiveness of a five-stage process of engagement with proven programmes and practices as a management tool for school leaders to address their schools' improvement agendas. The paper reports on the change process in each school over a one year period and the enablers and constraints associated with the concept of evidence-based practice as a driver for change in teaching and learning. The paper discusses the contribution the enquiry makes to a theory of learning where practitioners and researchers are equal partners in the learning process, and the relevance of this to managing school improvement through research use.